Synthesis of Composite Inhibitors and Their properties - Anvarova Zarina; Nazarov Sayfulla; Xolov Anvar; Baqoyeva Marjona (Peerian Journals Publishing, 2023)
This paper presents the synthesis and identification of (1,3-dioxoisoindolin-2- yl)methyl phosphoric acid and the corrosion rate and protection levels of the DIIMFK inhibitor Fon-1 in solution at various temperatures and concentrations
Keywords: Inhibitor; corrosion rate; plate; concentration